2017
DOI: 10.2807/1560-7917.es.2017.22.39.17-00206
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of mcr-1-bearing bacteria in the ecosystem, 2015 to 2016

Abstract: The recently discovered colistin resistance-encoding element, mcr-1, adds to the list of mobile resistance genes whose products rapidly erode the antimicrobial efficacy of not only the commonly used antibiotics, but also the last line agents of carbapenems and colistin. The relative prevalence of mcr-1-bearing strains in various ecological niches including 1,371 food samples, 480 animal faecal samples, 150 human faecal samples and 34 water samples was surveyed using a novel in-house method. Bacteria bearing mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 18 publications
3
48
2
3
Order By: Relevance
“…These results indicate that the resistance level of colistin in E. coli from children was different from that of adults. The 21 mcr-1 positive strains had higher resistance rates to tobramycin and doxycycline, 33.3% and 42.8%, respectively, than the other antibiotics, particularly carbapenem antibiotics; all isolates were sensitive to imipenem and meropenem, which is similar to observation in several other studies [11,18,19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results indicate that the resistance level of colistin in E. coli from children was different from that of adults. The 21 mcr-1 positive strains had higher resistance rates to tobramycin and doxycycline, 33.3% and 42.8%, respectively, than the other antibiotics, particularly carbapenem antibiotics; all isolates were sensitive to imipenem and meropenem, which is similar to observation in several other studies [11,18,19].…”
Section: Discussionsupporting
confidence: 87%
“…The mcr-1 gene is widely spread in Enterobacteriaceae, especially in K. pneumoniae and E. coli isolated from food sources, environment, and humans [3,25] In the present study, 18 strains successfully transmitted the mcr-1 gene to E. coli J53. Previous studies have shown that mcr-1 is present on many types of plasmids, such as IncI2, IncHI2, IncX4, etc.…”
Section: Discussionmentioning
confidence: 57%
“…E. coli and E. cloacae ) collected from urban surface water, rivers or lakes 3739 . This gene was reported from wastewater treatment plants in China 40 , in South Africa 41 , in Italia 42 , in Germany 43 or from hospital sewage water in China 44 . This variant was also reported from various bacteria isolated from other water environments, such as seawater in Algeria 45 , from top water in rural China 46 or from freshwater of intensive aquaculture in China 17 .…”
Section: Discussionmentioning
confidence: 95%
“…The persistence of MCR-1 in the human GI tract microflora can cause further contamination of the water systems through disposal of waste water containing human faeces. Fresh water systems outside these transmission routes remain clear of MCR-1 contamination [12].…”
Section: Spreading Ways or Routes Of Mcr-1 Transmissionmentioning
confidence: 99%